PWE-135 Pushing Propofol-Assisted Double Balloon Enteroscopy Out of Theatre and Into The Endoscopy Suite: Does The Pound Have Enough Pull?. (17th August 2016) - Ching, H-L; Branchi, F; Sanders, DS; Turnbull, D; Sidhu, R
Abstract : Introduction: Double balloon enteroscopy (DBE) has poorer tolerability compared to other forms of endoscopy due to procedure duration. Anaesthetic led propofol sedation in theatre is increasingly used for complex endoscopy however has cost implications. We studied the feasibility and cost effectiveness of providing an anaesthetic led propofol-based DBE service outside theatre. Methods: All patients undergoing DBE with propofol between March 2013 and December 2015 were prospectively recruited. The propofol lists were carried out in an endoscopy room with anaesthetists and fully equipped with anaesthetic equipment. Patient data including hospital anxiety and depression scores (HADS) were performed prior to DBE. Pain, discomfort and distress scores were measured post-DBE (range 0–10 for each category). Costs including consumables, staffing, ward and theatre expenses were compared. Results: A total of 82 patients (44% male, 79% oral DBE) were included (mean age 54±13 years). Indications for DBE included iron deficiency anaemia (37%), overt gastrointestinal bleeding (8.5%), Peutz-Jeghers syndrome (18%), abnormal radiology (2.4%), suspected Crohn's disease (22%), suspected coeliac complications (4.8%) and small bowel tumours/masses (6.1%). The mean dose of propofol was 1089 mg±422.9 and the mean procedural time 77 mins±25. The diagnostic yield was 63%. The findings included polyps/tumours (18%), angioectasias (22%), ulcers (12%), strictures (7%), and abnormal mucosa (6%). DBE was normal in 36.5%. DBE was well tolerated with median scores for pain, discomfort and distress all being 0.2. There were no correlations between pre-DBE HADS and post-DBE pain, discomfort or distress scores (p > 0.05 for all categories). Therapeutic intervention was performed in 40% which included argon plasma coagulation for angioectasias (13.4%), polypectomy (22%) and dilation of strictures (3.7%). One patient experienced transient bradycardia and required glycopyrrolate while another patient became wheezy and required nebuliser therapy post-procedure. Neither cases necessitated abandonment of DBE and were deemed non-serious adverse events. The cost of running a single DBE list with propofol is £2391 at our unit compared to a national range of £3174 - £4730 if run in theatre. Extrapolating this information would imply cost-savings of between £40, 700 - £110, 000 per year. Conclusion: We have demonstrated that propofol-assisted DBE in an endoscopy suite is safe and feasible. It provides excellent tolerability, irrespective of pre-DBE HADS and is cost effective for the department. This allows better utilisation of theatre resources and should be encouraged nationally for other forms of complex endoscopy. Disclosure of Interest: None Declared